MAKNA SIMBOLIK PANTUN DALAM TRADISI MULANG-MULANGKAN PADA MASYARAKAT MELAYU SAMBAS - Ahadi Sulissusiawan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to describe symbolic meanings of pantun in the mulang-mulangkantradition in the Sambas Malay community. The mulang-mulangkan tradition is a Malaytradition through which the parents of the bride and groom hand over the couple tofamilies and relatives to be well accepted. The study employed the ethnographic approachby applying the analysis according to the ethnographic framework by Spradley. Theanalysis was conducted by investigating symbols based on the contexts and relationalmeanings of folk terms in pantun in relation to the cultural life of the community possessingthe text. The results of the data analysis show that the folk terms in the Sambas Malaycommunity contain symbolic meanings. Some of them are advice on a pure bride, adviceon bitterness in family life, advice on loyalty and willingness to sacrifice, advice on patienceand trust in God to face life, advice on problem solving through agreement, advice ondiligence in saying prayers and not being lazy in family life, and advice on inviting otherswhen a baby is born.